Role of outpatient parenteral antibiotic therapy in the treatment of community acquired skin and soft tissue infections in Singapore - Chan, Monica (2018)
Background: Treatment of community acquired skin and soft tissue infections (SSTIs) is a common indication for outpatient parenteral antibiotic therapy (OPAT) in USA, UK and Australasia, however data from Asia are lacking. OPAT is well established within the Singapore healthcare since 2002, however, systematic use of OPAT for the treatment of SSTIs remains infrequent. In this report, we describe the treatment and outcome of patients with SSTIs referred directly from Emergency Department (ED) to OPAT for continuation of intravenous (IV) antibiotics in Singapore, thus avoiding potential hospital admission. Method: This is a single center university hospital retrospective study of patients with SSTIs presenting to ED who were assessed to require IV antibiotics and accepted to the OPAT clinic for continuation of IV treatment. Exclusion criteria were: haemodynamic instability, uncontrolled or serious underlying co-morbidities, necessity for inpatient surgical drainage, facial cellulitis and cephalosporin allergy. Patients returned daily to the hospital’s OPAT clinic for administration of IV antibiotics and review, then switched to oral antibiotics on improvement. Results: From 7 February 2012 to 31 July 2015, 120 patients with SSTIs were treated in OPAT. Median age was 56 years and 63% were male. Lower limbs were affected in 91%. Diabetes was present in 20%. Sixty-seven (56%) had been treated with oral antibiotics for a median duration of 3 days prior to OPAT treatment. Common symptoms were erythema (100%), swelling (96%), pain (88%) and fever (55%). Antibiotics administered were IV cefazolin with oral probenecid (71%) or IV ceftriaxone (29%) for median 3 days then oral cloxacillin (85%) for median 7 days. Clinical improvement occurred in 90%. Twelve patients (10%) were hospitalized for worsening cellulitis, with 4 patients requiring surgical drainage of abscess. Microbiological cultures from 2 patients with drained abscess grew methicillin sensitive Staphylococcus aureus (MSSA) and Klebsiella pneumoniae, both of which were susceptible to cefazolin and ceftriaxone. Hospital bed days saved was 318 days. Conclusion: OPAT treatment of community acquired SSTIs in a selected patient population has good outcomes in Singapore. Treatment with IV cefazolin or IV ceftriaxone was successful in the majority with low hospital readmission rate.